Complementary and Integrative Medicine in academic health education - Natasha Teixeira Medeiros; Ana Maria Fontenelle Catrib; Nelson Filice de Barros; Fabiane Elpídio de Sá; Guilherme Pinheiro Ferreira da Silva; Lidia Andrade Lourinho; Bernardo Diniz Coutinho; Raimunda Hermelinda Maia Macena; Paola Frassinetti Torres Ferreira da Costa; Ana Paula Vasconcellos Abdon (Elsevier, 2021)
Objective: To analyze academic education in Complementary and Integrative Medicine (CIM) according to university students from the health area. Methods: Cross-sectional study with 1399 students from six public and private Brazilian universities, with online and in-person collection of socioeconomic, demographic, educational and academic data, carried out in 2019. The bivariate analysis was applied for the outcome "presence of CIM in academic health education", using the SPSS Statistic program, version 23.0™. Results: The prevalence of the presence of CIM in academic health education was 52.3%, being 31.1% in the compulsory and 8% in the non-compulsory curricular education, 2.0% in scientific research and 4.7% in university extension activities. There was an association of the outcome with knowledge of the national CIM policy (OR = 5.258; p = 0.000), of which knowledge can be indicated and used in one's professional area (OR = 4.836; p = 0.000), interest and/or use of CIM by the teachers/tutors of the course (OR = 3.955; p = 0.000), stimulus by the university to carry out scientific research (OR = 3.277; p = 0.000) and university extension projects with CIM (OR = 3.686; p = 0.000). Conclusion: Academic education using CIM in health area courses is not very prevalent in teaching, research and university extension in Brazil, but when present in the curricular and non-curricular educational processes, it shows a significant association with knowledge, skills and their use by university students. The creation of a National Educational Planning in CIM is a vital imperative.